The push factors of young entrepreneur to be in industry / Zamri Muhammad - Muhammad, Zamri (2013)
The aim of the research was to study the push factors of young entrepreneur to be in industry in Kota Bharu. The contribution factors studied were income distribution, lifestyle, technology and capital resources. About 150 of young entreprenuer were participated in the survey. The data was analyzed using SPSS package version 20.0. The instrument of this study is questionnaire form and method that had used in this study is surveying through done by quota sampling. The dominant push factor of young entrepreneur to be in industry in this research was income distribution